2022
DOI: 10.3389/fcvm.2022.952953
|View full text |Cite
|
Sign up to set email alerts
|

Association of the systemic immune-inflammation index with all-cause mortality in patients with arteriosclerotic cardiovascular disease

Abstract: ObjectiveSystemic immune-inflammation index (SII), derived from blood cell counts of circulating platelets, neutrophils, and lymphocytes, has been identified as a novel inflammatory and prognostic marker. However, the clinical value of SII in patients with arteriosclerotic cardiovascular disease (ASCVD) had not been further explored. Thus, this study is designed to explore the associations of SII with mortality in ASCVD individuals.MethodsAll individuals with ASCVD aged ≥20 years were included from the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…SII was recognized as a valuable and convenient inflammatory biomarker to predict the risk of low bone mineral density or osteoporosis among postmenopausal women aged ≥ 50 years old ( 25 ). Moreover, SII has also been reported concerning all-cause mortality in arteriosclerotic cardiovascular disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…SII was recognized as a valuable and convenient inflammatory biomarker to predict the risk of low bone mineral density or osteoporosis among postmenopausal women aged ≥ 50 years old ( 25 ). Moreover, SII has also been reported concerning all-cause mortality in arteriosclerotic cardiovascular disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Li et al [ 13 ] suggested that high SII levels may increase overall mortality and cardiovascular disease mortality in the general population, using NHANES follow-up data from 1999 to 2014. He et al [ 12 ] showed a correlation between SII and all-cause mortality in the US arteriosclerotic cardiovascular disease (ASCVD) population. Increased SII was associated with poor survival in ASCVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated using a formula that takes into account the levels of certain immune system markers in the blood, The calculation formula is platelets × neutrophils ÷ lymphocytes [ 11 ]. The SII is often used as a predictor of mortality in patients with tumors, as higher SII values have been associated with an increased risk of death [ 10 , 12 , 13 ]. This may be related to the imbalance between the body’s tumor-promoting and anti-tumor factors in the tumor state.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study found that ln-SII at baseline was associated with all causes of death from any cause in the United States ASCVD population in the NHANES group [22]. Increased SII in ASCVD individuals is related to poor survival [23].In addition, higher levels of SII are related to an increased risk of hepatic steatosis[8], peripheral arterial disease [9], isolated coronary artery ectasia [10], urinary albuminuria excretion [5], diabetic kidney disease [11], and diabetic depression [12]. Likewise, T2DM patients were more likely to have elevated SII in our subgroup analysis compared with those who did not have T2DM, Indicating that in ammation may be signi cantly involved in developing T2DM.…”
Section: Discussionmentioning
confidence: 99%